On The Possibility of Utilising Zinc Oxide for Desulphurising Hot Metal - R. V. Kumar; F. Tailoka (Canadian Institute of Mining, Metallurgy and Petroleum, 2004)
In order to use ZnO laden dust as a possible desulphurization reagent, it is important to evaluate thermodynamics of the Zn-O-S system. At temperatures greater than 1450 K, there is an uncertainty in the thermodynamic data for the reaction of zinc with sulfur to form Zinc sulfide. In this work, the standard free energy has been determined using an electrochemical cell: Pt, Mo, MoO2/YSZ/ZnO, ZnS, S02, Pt., between 1198 and 1602 K. AG° varies from -145,880 to -88,100 J (± 2500) , with a phase change to ZnS (g) by sublimation occurring between 1450 and 1460 K. This is supported by thermogravimetric analysis which shows about 80% weight loss in ZnS from 1273 to 1473 K. Feasibility reactions were also performed and confirmed that ZnS (g) is formed when ZnO reacts with FeS (1473 to 1653 K) or with Fe-Csat-S(1473-1673 K). There is therefore potential for the utilization of ZnO laden waste as an additional or alternative reagent for desulfurisation.